Translation of chapters I, II, and III, pages 1-134 of the book "The elements of international law" by George B. Davis - Castillo Martínez, Ericka Alena
The first chapter of this book deals with the early beginnings and evolution of International Law. It explains the early codes, the types of law within international law, and the various twists and turns of history that led to International Law to developing the way it did. This is essential information as this branch of the Law was nonexistent many mihlennia ago and it has sbowly developed to be the norm. The advancement oftechnology, agriculture and trade eventuahly required a more defined structure to help avoid problems and wars between empires, countries, and kingdoms. The Roman Empire was one of the biggest contributors to the development of International Law with its development of Roman Law. Many centuries later, a German scholar named Hugo Grotius was the one who wrote, based on the way international relations were carried during his time and the Roman Law, invaluable work that is the base for the modern practice of the science. This led him to be arguably considered the father of International Law. Since Grotius' time, many other scholars have contributed to this science and allowed us to enjoy the benefits of laws and organizations that regulate international travel, relations, trade and commerce, etc. The second chapter of this book deals with the definitions and attributes of ah nations. There are many ways a nation can be structured and governed, many elements that must be clearly defined and regulated (boundaries, rivers, lakes, sea, etc.) Additionally, international relations between nations, territories and peoples can take different turns for which said nations must be ready. This chapter describes the phenomena and events that have happened and are likely to happen between nations, the precedents that have been set and how it affects how rulings are made to this day. Finaily, the third chapter of this book deals with the different rights nations inherently have and the duties they owe to other nations. This is the backbone of International Law, for if nations do not respect the rights of other nations or do not fulfihi their duties with other nations, confhicts will arise. These conflicts affect the inhabitants of these different territories in a great number of ways, and it is, precisely, to avoid them for which nations adhere themselves to organizations like the UN and must respect their duties and rights. Beyond the basic rights and duties nations owe each other, for nations to have amicable, positive relationships, they should also follow the amenities and ceremonial duties required by other nations. Although these are not strictly mandatory for any one nation, they are part of the demonstration of respect and peace that nations must have between each other. Despite all the benefits of modern International Law that we enjoy nowadays, it is still necessary for us to not take them fbr granted and to have a clear understanding of the history of humanity, our region and our countries. By comprehending our history and how different nations have interacted with each other in the past, we can become more well-rounded citizens of the world with authority based in knowledge to convey informed opinions and make decisions that will define the course of our future. For these reasons, having material like "The Elements of International Law with an account of its origin sources and historical development" by George B. Davis available to us is incredibly valuable. Despite this book's third edition having been published in 1908, it holds information and principies of International Law that are still the basis of the science and detailed recounts of many historical, international events that set precedent for the many more that wouid arise in the future as technology and humanity advanced. This book can be of great help, specially to students of International Law and Law students in general, as it was created to be a guide for these students to grasp the basic foundation of this intricate science from a credible source.